2021
DOI: 10.1111/acel.13443
|View full text |Cite
|
Sign up to set email alerts
|

The antagonistic pleiotropy of insulin‐like growth factor 1

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 45 publications
1
26
0
2
Order By: Relevance
“…Evidence has indicated that individuals with low IGF-1 could fail to exert neuroprotection against oxidative stress and neuroinflammation in the brain as a neurotrophic factor [25], and thus the activity of the GH-IGF-1 axis declines progressively with advancing age may be mechanistically involved in AD pathogenesis [26,27]. As for IGF-1 dysregulation in a high direction, Zhang et al suggested that IGF-1 interacts with age to modify hazards for dementia [28]. While IGF-1 can protect against dementia in younger individuals, it is conversely associated with an increased risk of dementia in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has indicated that individuals with low IGF-1 could fail to exert neuroprotection against oxidative stress and neuroinflammation in the brain as a neurotrophic factor [25], and thus the activity of the GH-IGF-1 axis declines progressively with advancing age may be mechanistically involved in AD pathogenesis [26,27]. As for IGF-1 dysregulation in a high direction, Zhang et al suggested that IGF-1 interacts with age to modify hazards for dementia [28]. While IGF-1 can protect against dementia in younger individuals, it is conversely associated with an increased risk of dementia in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…While IGF-1 can protect against dementia in younger individuals, it is conversely associated with an increased risk of dementia in the elderly. One possible mechanism is the inhibition of autophagy, which prevents core processes of repair and maintenance in the nervous system for older individuals [28].…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39][40] Using samples from the UK Biobank of nearly 450,000 people, Milman's group found that lower IGF-1 levels in younger people were associated with an increased risk of mortality and age-related diseases compared with older adults. 41 These data suggest an interaction between age and IGF-1, where higher levels of IGF-1 appear to be protective for younger adults but not for older adults. Milman contributes these effects to antagonistic pleiotropy of IGF-1, which promotes development and growth in youth but antagonizes proteostasis and other cell maintenance mechanisms at older age 42 (Fig.…”
Section: Translational Geroscience: Role Of Igf-1 In Human Healthspan and Lifespanmentioning
confidence: 81%
“…IGF-1 levels in vivo are regulated by GH, and IGF-1 also has a negative feedback regulation on GH secretion (161,162). Studies have shown that IGF-1 has important effects on the healthy growth and function of cells and tissue in model organisms (163)(164)(165). GH can not only directly affect human oocytes and cumulus cells but also indirectly influence oocyte quality and maintain oocyte DNA integrity by activating IGF-1 synthesis or promoting ovarian steroidogenesis (166-168).…”
Section: Gh/igf-1 Axis Interventionsmentioning
confidence: 99%